2021
DOI: 10.3390/healthcare9050586
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in Well-Being Based on Position in Elite Young Soccer Players during a Full Season

Abstract: The current study surveyed weekly and daily variations of well-being ratings relative to the Hooper Index (HI): fatigue (wFatigue), stress (wStress), delayed onset muscle soreness (wDOMS), and sleep quality (wSleep) during a soccer season based on players’ positions. The full-season was divided into three meso-cycles: Early season, week (W)1 to W7; Mid-season, W8 to W13, and End-season, W14 to W20. Twenty-six young players participated in the study (age, 15.5 ± 0.2 years; height, 172.9 ± 4.2 cm; body mass, 61.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 42 publications
3
19
2
Order By: Relevance
“…The players belong to a team that participated in UEFA Champions League. The participating players included the following field positions: four central defenders (CD), three wide defenders (WD), four central midfielders (CM), three wide midfielders (WM), and three strikers (ST) [ 14 ]. The inclusion criteria were regular participation in most of the training sessions (80 % of weekly training sessions), while the exclusion criteria include lack of player information, illness and/or injury for two consecutive weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The players belong to a team that participated in UEFA Champions League. The participating players included the following field positions: four central defenders (CD), three wide defenders (WD), four central midfielders (CM), three wide midfielders (WM), and three strikers (ST) [ 14 ]. The inclusion criteria were regular participation in most of the training sessions (80 % of weekly training sessions), while the exclusion criteria include lack of player information, illness and/or injury for two consecutive weeks.…”
Section: Methodsmentioning
confidence: 99%
“…However, the process of load monitoring over the full season, considering the playing posing, was few previously evidenced [10][11][12]. In fact, when the volume of training/competition increases in conjunction with insufficient recovery, the players may enter into an NFOR marked by decrements in performance due to cumulative fatigue during the season [13]. It has been shown that there are different performance level differences between player positions [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, controlling the physiological and physical condition of players provides information about their unique requirements [17]. Recognizing the demands is one of the key advantages of individual monitoring based on their playing position [13]. In addition, diverse energy systems, physiological, and psychological demands are represented by different roles and needs in each playing position [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, concerning the distance of sprint, Valquer et al [ 17 ] observed that 96% of sprints during a match are shorter than 30 m, with 49% of them being shorter than 10 m. So the ability to accelerate and maximum running speed are crucial in game performance. For this reason, coaches should take into account the development of these abilities relative to the age [ 18 ] and their stage of maturation [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hormones are stimulated during the period of puberty until full maturity is reached [ 22 ]. The increase in circulating hormonal levels improves neural function, coordination andpower and also produces both oxidative and non-oxidative changes in the metabolism [ 21 , 22 ]. Any inappropriate stimulus could cause some alteration in the development of the adolescent and that is why, the training loads should adapt to the speed of subject’s maturation [ 23 ].…”
Section: Introductionmentioning
confidence: 99%